Social and Economic Conditions of Rice Farmers in Ngrandu Village Ponorogo Regency in 2000-2024: Kondisi Sosial Ekonomi Petani Padi - Mahmudi, Agus Rahmat (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The purpose of this study is to analyze the social and economic life of farmers in Ngrandu Village in 2000-2024 and analyze the development of agriculture in Ngrandu Village in 2000-2024. This study uses historical research methods which include: Heuristics, Criticism, Interpretation, and Historiography. The results of this study are: Getting to know Ngrandu Village, Ponorogo Regency, The development of agriculture, especially rice farming in Ngrandu Village has changed in 2000-2024, the social conditions of rice farmers in Ngrandu Village have changed in 2000-2024, the economic conditions of rice farmers in Ngrandu Village have changed in 2000-2024. Thus it can be seen that rice farmers in Ngrandu Village have changed from time to time.